1974
DOI: 10.1002/bip.1974.360131203
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of hydrated collagen. II. Semiconductor properties

Abstract: SynopsisThe dc conductivity of hydrated bovine Achilles' tendon collagen has been determined as a function of hydration over a limited temperature range. At ambient temperature the conductivity changes from 10-l6 (Q cm)-l in the dry state to about lo-* (Q cm)-l at -24% water content by weight. For all temperatures the conductivity increases exponentially with hydration obeying s(h) = A exp(Oh), where h is a measure of the hydration, A is independent of temperature, and the parameter b -T-1. It is shown that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…The photochemical formation of dityrosine uses the absorbed photonic energy to accomplish tyrosyl radical formation. Ground state oxidation of tyrosine residues in collagen is most likely to involve water of hydration [15]. Our collagen samples, no doubt, were hydrated even in the solid state.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The photochemical formation of dityrosine uses the absorbed photonic energy to accomplish tyrosyl radical formation. Ground state oxidation of tyrosine residues in collagen is most likely to involve water of hydration [15]. Our collagen samples, no doubt, were hydrated even in the solid state.…”
Section: Discussionmentioning
confidence: 97%
“…Tomaselli et al [15] found that the adsorption of water onto solid bovine Achille's tendon (BAT) caused a dramatic increase on the values of dc conductivity σ that is both temperature-and hydration parameter (h)-dependent (as much as 8 orders of magnitude at h = 0.24). Increasing hydration decreases the activation energy, and moderate hydration levels, confer semiconductor-like properties on the collagen, with water possibly acting as an impurity [15]. Although the exact mechanism of tyrosyl formation is unclear, we can speculate that moderate hydration lowers the activation energy sufficiently to allow tyrosine oxidation via electron transfer (ET), proton transfer (PT), or proton-coupled electron transfer (PCET) (for review of PCET, see [16]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well described fact that hydration level influences electric conductivity of collagen. The increase in water content increases electric conductivity whereas the activation energy of charge conduction process is reduced [17,[30][31][32][33][34].…”
Section: Kubisz D Hojan-jezierskamentioning
confidence: 99%